مقاصد القران الكريم - بزيز رحمة; بركات مباركة; مايدي عبدالرحمان (جامعة عمار ثليجي الاغواط, 2024)
ملخص: في هذه الدراسة الموسومة بعنوان مقاصد القرآن الكريم –دراسة موضوعية- و التي توصلنا فيها الى بيان المقاصد القرآنية البارزة في الربع الأول (بداية من سورة البقرة وحتى الآية الثالثة من سورة الأعراف) و قد خلصنا إلى أنّ مقاصد القرآن الكريم هي الغايات التي أرادها الله عز وجلّ في كتابه بالإضافة إلى بيان هذه المقاصد القرآنية التي اشتمل عليها هذا الربع الأول وهي :المقاصد العقدية ،الإعجاز ،مقاصد التشريع ، مقاصد القصص و المواعظ و الإنذار فقد كانت هذه التقسيمات التي ارتكز عليها موضوع بحثنا والذي يبدأ بمقدمة ثم الفصل الأول المعنون بمصطلحات ومفاهيم والفصل الثاني الذي كان عنوانه مقاصد القرآن الكريم و أخيرا انتهى بخاتمة. كلمات افتتاحية: مقاصد القرآن الكريم، الطاهر بن عاشور ، الربع الأول. Summary: In this study entitled The Objectives of the Holy Qur’an - an objective study - in which we have reached a statement of the prominent Qur’anic objectives in the first quarter (beginning from Surat Al-Baqarah until the third verse of Surat Al-A’raf) and we have concluded that the objectives of the Holy Qur’an are the goals that God Almighty wanted. And in his book، in addition to explaining these Qur’anic objectives that are included in this quarterit is the following: The objectives of the doctrine، the miracle، the objectives of legislation، the objectives of stories، sermons، and warnings. These were the divisions upon which the subject of our research was based، which begins with an introduction، then the first chapter entitled with terms and concepts، the second chapter، which was entitled the objectives of the Holy Qur’an، and finally، it ended with a conclusion.
دراسة موضوعية